Políticas públicas voltadas para educação ambiental em zonas costeiras nacionais e das regiões do Estado do Pará : uma revisão bibliográfica - SANTOS, Thatiane Cunha Andrade dos (2022)
This research presents a study about the existence and creation of public policies aimed at environmental education regarding the Coastal Zones of Brazil and more specifically in regions of the State of Pará. - it is necessary to understand how they can and should interfere in the process of the multiplicity of uses of these spaces, in order to reflect critically on this subject, in order to develop strategies for these public policies to be effectively implemented, as well as its implications, both in the national and regional context of the State of Pará. This study aims to critically analyze the actions of environmental education related to public policies. This study is a bibliographic review. Sources that were capable of responding to the problem of work were identified, taking into account those that contained information on Public Policies for Environmental Education in Coastal Zones at national and regional level. And for this, a survey was carried out, through the virtual databases: SCIELO, LILACS and EduBases. Thus, all the objectives proposed in that work were achieved, since it was possible to critically analyze the actions of environmental education related to public policies, as well as to identify which of these policies are aimed at the coastal zone of Pará and which are part of the national plan, emphasizing possible strategies for the development of these policies. Keywords: environmental education; public policy; coastal zones.